2022
DOI: 10.1039/d2bm01181f
|View full text |Cite
|
Sign up to set email alerts
|

A polymeric IDO inhibitor based on poly(ethylene glycol)-b-poly(l-tyrosine-co-1-methyl-d-tryptophan) enables facile trident cancer immunotherapy

Abstract: A polymeric IDO inhibitor has been developed for the first time from copolypeptides for facile trident cancer immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Using electron microscopy to analyze OMV morphology, Schulz et al also discovered that OMVs are biocompatible with differentiated macrophages and epithelial cells [ 87 ]. Thirdly, both PVs and OMVs can easily be loaded with the drug compound and protect it [ 88 , 89 ]. Fourthly, both PVs and OMVs can easily deliver drugs to target sites.…”
Section: Drug Delivery Performance Of Pvs and Omvsmentioning
confidence: 99%
“…Using electron microscopy to analyze OMV morphology, Schulz et al also discovered that OMVs are biocompatible with differentiated macrophages and epithelial cells [ 87 ]. Thirdly, both PVs and OMVs can easily be loaded with the drug compound and protect it [ 88 , 89 ]. Fourthly, both PVs and OMVs can easily deliver drugs to target sites.…”
Section: Drug Delivery Performance Of Pvs and Omvsmentioning
confidence: 99%
“…The NPs show the stability of long circulation in blood circulation, but the response to low pH acidic environment in TME makes the drug release rapidly [ 128 ]. In addition, a polymeric indoleamine-(2,3)-dioxygenase (IDO) inhibitor based on the poly(ethylene glycol)-b-poly(L-tyrosine-co-1-methyl-D-tryptophan) copolymer (PEG-b-P(Tyr-co-1-MT)) was developed for facile trident cancer immunotherapy [ 129 ]. The polymeric IDO inhibitor was modified by Cyclo (Arg–Gly–Asp–D–Tyr–Lys) peptide (cRGD), which can bind to α v β 3 intergrin for targeting tumor cells.…”
Section: The Nanocarriers For Cancer Targeting Therapymentioning
confidence: 99%
“…Previously, in order to improve the reaction rate and make the drug completely released to the target site, the dual response nanocarriers have been developed to respond to the combination of two signals (e.g., pH/temperature, pH/redox, and photo/temperature) [ 129 , 130 , 131 , 132 ]. Therefore, these novel double response nanocarriers have been proved to be anti-cancer drug delivery platforms that can be used for drug control release and targeting of tumor sites, which has a very favorable prospect for the treatment of solid tumors.…”
Section: The Nanocarriers For Cancer Targeting Therapymentioning
confidence: 99%
“…20−23 To achieve synergistic and potent treatment, the ideas of the co-delivery system have been designed and acquired remarkable therapeutic outcomes. 24,25 It has been reported that the combination of flavonoid compounds like Hes with 5-fluorouracil, CDDP, and paclitaxel can effectively improve the cytotoxicity of anti-tumor drugs. 26,27 In parallel, Hes can inhibit the PI3K/Akt signaling pathway 28 and reduce the expression of matrix metalloproteinases (MMPs), 29 an important mesenchymal cell marker, implicating that the combined administration of Hes with CDDP may achieve better inhibitory effects on tumor growth and metastasis if these two drugs could be specifically co-delivered to the tumor site efficiently.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multiple large doses of CDDP or repeated administration within a short period of time may cause irreversible renal dysfunction and, in severe cases, lead to renal tubular necrosis. , Hesperetin (Hes), a kind of edible dihydroflavonoid compound that widely exists in citrus fruits, is easily available but with low solubility and bioavailability. Hes has been shown to have anti-cancer activity in gastric cancer, malignant glioma, prostate cancer, lung cancer, and other tumors by inhibiting cell proliferation and promoting cell cycle arrest or apoptosis. To achieve synergistic and potent treatment, the ideas of the co-delivery system have been designed and acquired remarkable therapeutic outcomes. , It has been reported that the combination of flavonoid compounds like Hes with 5-fluorouracil, CDDP, and paclitaxel can effectively improve the cytotoxicity of anti-tumor drugs. , In parallel, Hes can inhibit the PI3K/Akt signaling pathway and reduce the expression of matrix metalloproteinases (MMPs), an important mesenchymal cell marker, implicating that the combined administration of Hes with CDDP may achieve better inhibitory effects on tumor growth and metastasis if these two drugs could be specifically co-delivered to the tumor site efficiently.…”
Section: Introductionmentioning
confidence: 99%